Retinal and Preretinal Hemorrhages in a Patient Receiving Hyper-CVAD Chemotherapy for T-Cell Acute Lymphoblastic Leukemia - Krishi Peddada; Stephanie J. Weiss; Shaina Kumar; Deepika Malik (Case Reports in Ophthalmological Medicine)
Hyperfractionated cyclophosphamide, vincristine, adriamycin, and dexamethasone (Hyper-CVAD) is an important chemotherapeutic regimen for acute lymphoblastic leukemia (ALL) and non-Hodgkin’s lymphoma. We present a case of a 23-year-old male with T-cell ALL and visual acuity of 20/20 in the right eye and 20/25 in the left eye who developed significant changes in his vision after starting Hyper-CVAD therapy. The patient initially presented with cotton wool spots in the fundus shortly after starting the regimen. After going through the induction phase of chemotherapy, he had a sudden decline in his vision to light perception in the left eye. Posterior segment exam revealed retinal ischemia and multilayered hemorrhages in both eyes as well as a large preretinal hemorrhage obscuring the fovea in the left eye. Labs associated the appearance of these hemorrhages with a significant decrease in hemoglobin and a platelet count of 5 K/μL. A Nd:YAG laser applied in the left eye at the posterior hyaloid face allowed blood to drain into the vitreous cavity and brought the patient’s visual acuity back to baseline. Hyper-CVAD is an aggressive chemotherapy regimen that can cause severe thrombocytopenia secondary to myelosuppression. Frequent retinal evaluations and timely intervention is advisable in these cases as extensive intraretinal hemorrhages may cause irreversible damage.